A comparison on classical-hybrid conjugate gradient method under exact line search - Shazlyn Milleana Shaharudin (Tanjong Malim, 2019)
A comparison on classical-hybrid conjugate gradient method under exact line search by Shazlyn Milleana Shaharudin